IMPLEMENTASI PROGRAM PELAYANAN TEMUKAN, OBATI SAMPAI SEMBUH PENDERITA TUBERKULOSIS (TOSS-TB) DI PUSKESMAS SELABATU KOTA SUKABUMI - Annisa Nur Zannah; Dian Purwanti; Tuah Nur (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
In 2022 Sukabumi City experienced a significant increase in TB cases from 1,256 to 1,602 cases. In addition, there is still a negative stigma from the community towards TB and its sufferers. To overcome TB cases, the Sukabumi City Government has attempted to implement a TB control program policy, namely the Find, Treat Until Cured Tuberculosis Patients (TOSS-TB) program. This study aims to determine the implementation of the TOSS-TB Program from prevention to cure at the Selabatu Health Center in Sukabumi City with the research process carried out referring to the theory of policy implementation with analysis indicators namely policy accuracy, implementation accuracy, target accuracy, environmental accuracy and process accuracy. The research method used was descriptive qualitative using purposive sampling technique and the number of respondents was six informants. The results of this study are in the implementation of the TOSS-TB program in the Selabatu Health Center area of Sukabumi City both from the accuracy of the policy, the implementation carried out and the accuracy of the planned targets, as well as the environmental accuracy of the implementation then the process carried out is still not quite in accordance with the TOSS-TB program policy in its implementation. Recommendation suggestions for the implementation of the TOSS-TB program include increased cooperation with stakeholders or cross-sectors such as special hospitals for TB treatment and community organizations to break the chain of TB spread, in addition to increasing the provision of information to the public about TB and TB patients along with optimizing mass media publications to socialize about TB prevention.